Synthesis and Characterisation of Zinc-doped Antimony Selenide - Jumah, Thamir A.; Wadi, Kassim M.; Chillab, Riyadh K.; Abdul-Kareem, Hikmat N. (Iraqi Journal of Science, 2021)
Antimony selenide substituted with Sb0.4Se0.6 and doped with zinc at three doping ratios (x=0, 0.01 and 0.03) was prepared via the solid state reaction method. The three prepared compositions were reacted thermally at 400 °C for 3 h. The structure of specimens was characterised via X-ray powder diffractometer to obtain the type of crystalline structure and lattice parameters of the prepared specimens, which showed a polycrystalline, orthorhombic structure. Optical characterisation was then achieved via UV-visible spectroscopy to exhibit the transmittance and reflectance spectra and estimate the band gap values of the prepared compositions. The samples showed high absorption spectra at low wavelengths (from 60% to 90%) and low reflectance values (from nearly zero to 17%). The band gap measurement showed an indirect transition, with values ranging from 1.2 eV to 1.23 eV. The electrical characteristics were represented by DC resistivity measurement at low temperature and AC conductivity measurement against frequency. The compositions showed a semiconducting behaviour in DC resistivity and compatible results in AC conductivity.